Combining an active method and a passive method in cooling lithium-ion batteries and using the generated heat in heating a residential unit. (May 2022) - Almehmadi, Fahad Awjah; Alqaed, Saeed; Mustafa, Jawed; Jamil, Basharat; Sharifpur, Mohsen; Cheraghian, Goshtasp
Highlights: Cooling lithium-ion batteries by combining an active method and a passive method Airflow is simulated among cylindrical lithium-ion batteries cells using COMSOL software. Using the PCMs to control the temperature of the lithium-ion batteries Using more battery cells and air speeds can provide more energy to the building. Abstract: In this paper, a gentle air flow is simulated among cylindrical lithium-ion battery (LIIB) cells using COMSOL software. A circular PCM compartment is placed around the battery cells. The hot air from cooling the battery is used to heat the house. By changing the battery position in three modes in PCM in the air speed range of 1 × 10 −3 to 5 × 10 −3 m/s, the volume fraction of solid PCM, the average PCM temperature ( T A v e − P C M ), the maximum battery temperature ( T m a x − b ) and the exhaust air temperature at different times from 0 to 1000 seconds are analyzed. The percentage of time energy provided by this system of the total energy required for this residential house has also been examined. The results of this study show that over time at high speeds, the T m a x − b of the LIIB first increases and then decreases. The passage of time also reduces the amount of T O u t l e t . If the LIIB is placed on the air inlet side of the PCM instead of the air outlet side, the T m a x − b is reduced by 1.53 degrees at high speeds. Placing the LIIB on the left side of the PCM causes the output temperature ( T O u t l e t ) to be higher and also increases the amount of solid PCM by up to 5% in 1000 seconds compared to placing the LIIB on the right side. Using 50 cells of LIIB and air flow of 0.005 m/s in this system can provide up to 22% of the required energy for heating the building in a winter day. Graphical abstract: Image, graphical abstract